Electronic functional component, strain sensor, and method for manufacturing electronic functional component

A polyurethane nanofiber network coated with silicone resin and gold enhances stretch resistance, enabling accurate measurement of soft body surfaces with reduced discomfort.

JP7602263B2Active Publication Date: 2024-12-18THE UNIV OF TOKYO
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021512326
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-03
Filing Date
2020-04-03
Publication Date
2024-12-18
Estimated Expiration
2040-04-03

AI Technical Summary

Technical Problem

Existing flexible electronics lack sufficient stretch resistance when directly attached to the skin, limiting their ability to accurately measure biological information without causing discomfort.

Method used

A nanofiber network made of polyurethane is coated with a silicone resin (PDMS) to form a nanomesh electrode, which includes a conductive gold film, enhancing stretch resistance and flexibility.

Benefits of technology

The nanomesh electrode demonstrates improved resistance to expansion and contraction, allowing accurate measurement of soft, non-planar shapes like the human body surface with minimal discomfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602263000002
    Figure 0007602263000002
  • Figure 0007602263000003
    Figure 0007602263000003
  • Figure 0007602263000004
    Figure 0007602263000004
Patent Text Reader

Abstract

[Problem] To provide an electronic functional member having high stretch-resistance. [Solution] An electronic functional member provided with: fibers formed in web-like shape and configuring a fiber web; a coating film coating the fibers and having a Young's modulus smaller than that of the fibers; and an electrically conductive film formed on the surface of the coating film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electronically functional member and a strain sensor formed using the electronically functional member. [Background technology]

[0002] In recent years, flexible electronics has been attracting a lot of attention due to its various applications, which are possible due to the softness of the materials. In particular, interest in the field of healthcare has been growing due to the aging of society worldwide. For example, flexible electronics have attracted attention as a means of directly obtaining biological information from cells and tissues by attaching them to the surface or inside of the human body.

[0003] In general, flexible electronics are produced by forming electronic devices on a flexible substrate, but the flexibility of the substrate is not sufficient, and the conformability to the surface is not sufficient, making it difficult to obtain highly accurate information or to sufficiently reduce discomfort when worn.

[0004] In order to solve these problems, an electronic functional component has been proposed that has sufficient surface conformability, lateral extensibility, gas and moisture permeability, and transparency, by forming a nanofiber network made of water-soluble polyvinyl alcohol (PVA) by electrospinning, and then forming an electrode layer by vapor-depositing gold on top of the network (e.g., Non-Patent Document 1). [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Akihito Miyamoto et.al.,Nature Nanotechnology 12,907(2017) Summary of the Invention [Problem to be solved by the invention]

[0006] However, when the electronic functional members of the above-mentioned conventional techniques are used by directly attaching them to the skin, there is room for improvement in terms of stretch resistance.

[0007] Therefore, the inventors of this application conducted intensive research and discovered that stretch resistance could be improved by coating a fiber network made of one type of resin with another resin.

[0008] The present invention has been made in view of the above-mentioned points, and an object of the present invention is to provide an electronic functional member and a strain sensor having improved resistance to expansion and contraction. [Means for solving the problem]

[0009] In order to achieve the above-mentioned object, the electronic functional component of the present invention is configured to include fibers formed in a mesh shape constituting a fiber network, a coating film that covers the fibers and has a lower Young's modulus than the fibers, and a conductive film formed on the surface of the coating film.

[0010] In addition, the strain sensor of the present invention comprises a detection unit, a measurement unit, and an output unit. The detection unit is attached to the object to be measured and is a part whose electrical resistance value changes depending on the shape of the object to be measured or a change therein. The measurement unit measures the electrical resistance value of the detection unit and sends the electrical resistance value to the output unit. The output unit outputs a predetermined signal based on the electrical resistance value received from the measurement unit. Effect of the Invention

[0011] According to the electronic functional member and strain sensor of the present invention, the fiber net made of one type of resin is coated with another type of resin, thereby improving the stretch resistance. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram for explaining a nanomesh electrode. [Diagram 2] FIG. 1 shows the evaluation results of stretch resistance. [Diagram 3]FIG. 2 shows the evaluation results of stretch resistance. [Figure 4] FIG. 2 is a schematic diagram of a strain sensor. [Diagram 5] This is an image of a nanomesh electrode obtained by SPM. [Figure 6] FIG. 13 is a diagram for explaining measurement of changes in electrical resistance value of a nanomesh electrode. [Figure 7] FIG. 2 is a schematic diagram for explaining a method for measuring an electrical resistance value. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described with reference to the drawings, but the shape, size, and positional relationship of each component are merely shown in a schematic manner to allow the present invention to be understood. In addition, the following describes a preferred configuration example of the present invention, but the material and numerical conditions of each component are merely preferred examples. Therefore, the present invention is not limited to the following embodiment, and many changes or modifications can be made that can achieve the effects of the present invention without departing from the scope of the configuration of the present invention.

[0014] (Nanomesh electrode) A nanomesh electrode as an electronic functional component according to the present invention will be described with reference to Fig. 1. Fig. 1 is a schematic diagram for explaining a nanomesh electrode. Figs. 1(A) to (C) are schematic configuration diagrams of the nanomesh electrode, and Figs. 1(D) to (F) are schematic cross-sectional views of fibers of the nanomesh electrode.

[0015] The electronic functional component is configured to include fibers 20 arranged in a mesh shape to form a sheet-like fiber mesh 10, a coating film 30 that coats the fibers 20, and a conductive film 40 formed on the surface of the coating film 30.

[0016] Polyurethane is used as a core material constituting the fibers 20. In this case, the fiber network 10 is formed by electrospinning using a 13 wt % polyurethane solution. As a solvent for this polyurethane solution, for example, a 7:3 mixed solution of N,N-dimethylformamide and methyl ethyl ketone is used. The conditions of the electrospinning method for forming the fiber network 10 can be a spinning time of 30 minutes, an applied voltage of 25 kV, and a discharge rate of 1 ml / hour. After performing the electrospinning method, ultraviolet (UV) ozone treatment is performed for 1 minute to obtain the fiber network 10 (see FIGS. 1(A) and (D)).

[0017] The diameter of the fiber 20, in this example, the polyurethane fiber, is preferably within a range of 100 nm to 1 μm, and more preferably within a range of 200 nm to 700 nm. In this case, the polyurethane fiber is a so-called nanofiber. The Young's modulus of polyurethane is 100 MPa to 700 MPa, which is relatively high.

[0018] Here, an example in which polyurethane is used as the core material has been described, but the present invention is not limited to this. Any material that can form a nanofiber fiber network by electrospinning may be used as the core material. This is because it is difficult to create a nanofiber fiber network with a material that has a very low Young's modulus. In addition to polyurethane, for example, polyvinyl alcohol (PVA) derivatives, polyvinylidene fluoride (PVDF), etc. can be used as the core material.

[0019] A silicone resin, for example, polydimethylsiloxane (PDMS), is used as a coating material constituting the coating film 30. In this case, the coating film 30 is formed by dip-coating the fiber with a PDMS solution. This PDMS solution is obtained by dissolving a PDMS precursor in hexane. The weight ratio of the PDMS precursor to hexane is, for example, 1:100.

[0020] The thickness of the coating film 30 is preferably within a range of 30 nm to 300 nm, and more preferably within a range of 70 nm to 150 nm. The Young's modulus of PDMS is generally 4 MPa to 40 MPa, which is relatively low (see FIGS. 1(B) and (E)).

[0021] Here, an example in which PDMS is used as the covering material has been described, but the covering material is not limited to this. A material with a low Young's modulus is preferable as the covering material. In addition to PDMS, for example, ethylene vinyl acetate (EVA) resin can be used as the covering material.

[0022] Gold (Au) is used as the conductive material constituting the conductive film 40. In this case, the conductive film 40 is formed by vacuum-depositing Au onto the coated fiber net 11 in which the coating film 30 is formed on the fibers 20. Here, when the conductive film 40 is formed from both sides of the sheet-like coated fiber net 11, the conductive film 40 is formed on the entire surface of the fibers 20 coated with the coating film 30. As a result, the nanomesh electrode 12 is obtained.

[0023] 1(C), the conductive film 40 is provided on both sides of the nanomesh electrode 12, but this is depicted for convenience in order to show the surface on which the conductive film 40 is formed. Also, in other figures, this may be depicted for convenience in order to show the surface on which the conductive film 40 is formed. Note that the conductive film 40 may be formed only on one side of the sheet-like coated fiber netting 11.

[0024] The thickness of the conductive film 40 is preferably within a range of 30 nm to 300 nm, and more preferably 70 nm to 150 nm.

[0025] Here, an example in which Au is used as the conductive member has been described, but the conductive member is not limited to this. In addition to Au, silver (Ag), titanium (Ti), platinum (Pt), etc. can be used as the conductive member. The method of forming the conductive film is not limited to vacuum deposition. The conductive film can be formed by sputtering, spin coating, slit coating, or screen printing using a dispersion of the conductive member.

[0026] (Evaluation of stretch resistance) The evaluation of the stretch resistance of the nanomesh electrode will be described with reference to Figures 2 and 3. Figures 2 and 3 are diagrams showing the evaluation results of stretch resistance.

[0027] The stretch resistance was evaluated as follows. First, a PDMS layer was formed on a glass substrate to a thickness of 200 μm. Next, an adhesive layer was formed on the PDMS layer. The adhesive layer was formed by spin-coating liquid PDMS to a thickness of 100 nm. Next, the nanomesh electrode to be evaluated was attached to the adhesive layer. After the liquid PDMS was dried, the glass substrate was peeled off. The stretch resistance of the nanomesh electrode attached to the 200 μm thick PDMS layer obtained in this way was evaluated.

[0028] In Figure 2(A), the horizontal axis shows the elongation (%) of the nanomesh electrode, and the vertical axis shows the rate of change in electrical resistance ΔR / R (%). Here, an elongation of 60% means that the length of the nanomesh electrode in the elongation direction has increased by 60% from the initial state before elongation, that is, it has increased by 1.6 times.

[0029] Figure 2(A) shows the difference in the fiber network structure. In Figure 2(A), curve I shows the case where the fiber is made of PVA derivative and no coating is provided, curve II shows the case where the core material is polyurethane (PU) and the coating material is PDMS, curve III shows the case where the core material is polyurethane and the coating material is polyparaxylene, and curve IV shows the case where the fiber is made of polyurethane and no coating is provided.

[0030] Here, the Young's modulus of polyparaxylene is 2 GPa to 3 GPa, which is higher than that of polyurethane.

[0031] In all cases of curves I to IV, the resistance value increases gradually as the elongation increases. When the fiber is made of a PVA derivative (curve I), the resistance value increases rapidly at approximately 50% elongation, i.e., the fiber breaks. On the other hand, when the fiber is made of polyurethane (curves II to IV), the resistance value increases rapidly when the elongation reaches approximately 150% or more. Thus, when the fiber is made of polyurethane, the stretch resistance is improved compared to when the fiber is made of a PVA derivative.

[0032] Figures 2(B) to (E) show the results of a stretching cycle test on a nanomesh electrode corresponding to curves I to IV in Figure 2(A), respectively. In Figures 2(B) to (E), the horizontal axis shows the repeating period in units of 100 cycles, and the vertical axis shows the rate of change in electrical resistance ΔR / R (%). Here, stretching (30%) and relaxation (0%) are repeated.

[0033] When the fiber is made of a PVA derivative as in Fig. 2(B), and when the core material is polyurethane and the coating material is polyparaxylene as in Fig. 2(D), the rate of change in electrical resistance ΔR / R (%) varies with each repetition period. When the fiber is made of polyurethane as in Fig. 2(E) and no coating film is provided, the rate of change in electrical resistance ΔR / R (%) varies little with each repetition period, but the value of the rate of change in electrical resistance ΔR / R (%) increases as the number of repetitions increases.

[0034] In contrast, when the core material in Figure 2(C) is polyurethane (PU) and the coating material is PDMS, the variation in the rate of change in electrical resistance per repetition cycle, ΔR / R (%), is small. Moreover, even if the number of repetitions increases, the rate of change in electrical resistance, ΔR / R (%), remains almost constant.

[0035] In this way, by using polyurethane (PU) as the core material and PDMS as the covering material, excellent stretch resistance has been demonstrated.

[0036] Figure 3 shows a nanomesh electrode with a core material of polyurethane (PU) and a coating material of PDMS, in which a conductive film is provided on both sides of the sheet-shaped coated fiber mesh (I) and a conductive film is provided on only one side of the sheet-shaped coated fiber mesh (II).

[0037] In both cases (I) where a conductive film is provided on both sides and (II) where a conductive film is provided on only one side, the resistance value increases gradually as the elongation increases. In the case of (II) where a conductive film is provided on only one side, the resistance value increases suddenly at an elongation of about 60%, i.e., the wire breaks. On the other hand, in the case of (II) where a conductive film is provided on both sides, the resistance value increases gradually until the elongation is about 150%, and then increases suddenly when the elongation exceeds 150%. Thus, when a conductive film is provided on both sides, better stretch resistance can be obtained than when a conductive film is provided on only one side.

[0038] (Method of attaching nanomesh electrodes) The nanomesh electrode, which is the electronic functional component according to the present invention, is made of a water-soluble material and is not formed into fibers, so it cannot be attached by simply placing the nanomesh electrode on the surface of the measurement target, such as the skin, and then exposing it to water vapor.

[0039] Three methods will be described as examples of methods for attaching nanomesh electrodes to the skin.

[0040] In the first method, a 10% by weight PVA aqueous solution is applied to the skin, and before the PVA dries, a nanomesh electrode is attached to the PVA. In the second method, a fiber net made of PVA as a resin material is formed by electrospinning, and then a nanomesh electrode is laminated. The PVA fiber net is then placed in contact with the skin and exposed to water vapor. In this method, the fiber net made of PVA as a resin material is attached to the skin by utilizing the fact that part or all of the fiber net is water-soluble. In the third method, a PVA film is produced by spin coating at 500 rpm using a 10% by weight PVA aqueous solution, and this PVA film is attached to the skin. A nanomesh electrode is placed on the PVA film, and exposed to water vapor in the same manner as in the second method. By these first to third methods, a nanomesh electrode can be attached to the skin.

[0041] (Distortion sensor) A strain sensor using this nanomesh electrode will be described with reference to Figure 4. Figure 4 is a schematic diagram of the strain sensor.

[0042] The strain sensor is configured to include, for example, a detection unit 110, a measurement unit 120, and an output unit 130. The detection unit 110 is attached to the measurement object 200, and is a part whose electrical resistance value changes according to the shape of the measurement object 200 or a change therein. The measurement unit 120 measures the electrical resistance value of the detection unit 110 and sends the electrical resistance value to the output unit 130. The output unit 130 outputs a predetermined signal based on the electrical resistance value received from the measurement unit 120. The measurement unit 120 and the output unit 130 can be configured as desired and suitably by a person skilled in the art, and therefore detailed explanations thereof will be omitted here.

[0043] The detection unit 110 is composed of a nanomesh electrode. In the following description, the detection unit and the nanomesh electrode may be denoted by the same reference numeral 110.

[0044] In the nanomesh electrode 110, a conductive film 40 is formed on the surface of non-conductive fibers. The fibers also form a mesh-like fiber network. In this case, when the nanomesh electrode 110 is stretched, the area occupied by the fibers per unit area (hereinafter referred to as fiber density) decreases, and the number of contact points of the conductive film decreases. If the number of contact points of the conductive film decreases, the electrical resistance increases. On the other hand, when the nanomesh electrode 110 is compressed, the fiber density increases, and the number of contact points of the conductive film increases. If the number of contact points of the conductive film increases, the electrical resistance decreases.

[0045] In this way, the electrical resistance changes due to the expansion and contraction of nanomesh electrode 110. Therefore, by attaching nanomesh electrode 110 to measurement object 200 and measuring the electrical resistance, the shape of the object and changes therein can be measured.

[0046] Conventional strain sensors cannot measure the shape or changes of soft or non-flat surfaces such as curved surfaces, making it difficult to follow and measure the movements of living organisms such as muscles.

[0047] In contrast, according to the strain sensor of this embodiment, the detection unit 110 attached to the object to be measured 200 is composed of a fiber network, so that it is possible to measure the shape and changes of even soft, non-flat objects to be measured, such as the surface of a living body.

[0048] The thickness dependency of the nanomesh electrode used as the detection unit 110 of the strain sensor will be described. In this example, a nanomesh electrode made of a PVA derivative is used to evaluate the thickness dependency.

[0049] Two types of nanomesh electrodes were created: one with a thickness of 7 μm and one with a thickness of 10 μm. As the diameter of the fibers (nanofibers) that make up the nanomesh electrodes is approximately 500 nm, the 7 μm nanomesh electrode has a layer structure of approximately 14 layers, and the 10 μm nanomesh electrode has a layer structure of approximately 20 layers.

[0050] In addition, two types of conductive films, one with a thickness of 50 nm and the other with a thickness of 75 μm, were created for each of the nanomesh electrodes with thicknesses of 7 μm and 10 μm.

[0051] The microscopic electrical conduction state of the fabricated nanomesh electrode was observed using a scanning probe microscope (SPM).

[0052] Figure 5 shows images of a nanomesh electrode taken with an SPM. Figure 5(A) is an image taken in normal measurement mode, and Figure 5(B) is an image showing the region where the conductive film of the reference region, which serves as a reference for measuring electrical resistance, is electrically connected to the conductive film of the nanomesh electrode to be measured.

[0053] 5(A) and 5(B), it can be seen that there are conductive films that are conductive with the reference region and conductive films that are not conductive with the reference region. The non-conductive conductive films are thought to be caused by a certain fiber being in the shadow of other fibers on the surface side, so that the conductive film is not vapor-deposited and the conductive film of the uppermost fiber is not conductive.

[0054] The change in electrical resistance value when stress is applied to the nanomesh electrode will be described with reference to Fig. 6. Fig. 6 is a diagram for explaining the measurement of the change in electrical resistance value of the nanomesh electrode. Fig. 6(A) is a schematic diagram of the measurement system, and Fig. 6(B) and (C) show the screen of an oscilloscope displaying the change in electrical resistance value.

[0055] Here, a 100 Ω fixed resistor 140 was connected in series to the nanomesh electrode 110, a voltage was applied to one end of the fixed resistor that was not connected to the nanomesh electrode 110, the one end of the nanomesh electrode 110 that was not connected to the fixed resistor 140 was grounded, and the other end of the fixed resistor 140 was connected to the other end of the nanomesh electrode 110, and the voltage at the connection point between the fixed resistor 140 and the nanomesh electrode 110 was measured.

[0056] FIG. 6(B) shows the voltage change when compressive stress and tensile stress are repeatedly applied to the nanomesh electrode, and FIG. 6(C) shows the voltage change when the nanomesh electrode is repeatedly twisted.

[0057] As shown in Figures 6(B) and (C), it can be seen that by applying various stresses to the nanomesh electrode, the measured voltage changes, that is, the resistance of the nanomesh electrode changes.

[0058] The electrical resistance values ​​when a tensile stress and a compressive stress are applied will be described with reference to Fig. 7 and Table 1. Fig. 7 is a schematic diagram for explaining a method for measuring the electrical resistance value.

[0059] [Table 1]

[0060] Table 1 shows the electrical resistance values ​​when compressive stress and tensile stress were applied to two types of nanomesh electrodes, one with a 50 nm thick conductive film and one with a 75 μm thick conductive film, for the 7 μm thick and 10 μm thick nanomesh electrodes, respectively.

[0061] Here, the conductive film is provided only on one of the main surfaces of the fiber network. The nanomesh electrode is cut into a rectangular shape with a width of 5 mm and a length of 30 mm, and is attached to a cylinder 210 with a radius of 20 mm. By attaching the surface on which the conductive film 40 is provided to the cylinder 210, a compressive stress is applied to the fiber network 12 on the side on which the conductive film 40 is formed (see FIG. 7(A)). In addition, by attaching the surface opposite to the surface on which the conductive film 40 is provided to the cylinder 210, a tensile stress is applied to the fiber network 12 on the side on which the conductive film 40 is formed (see FIG. 7(B)).

[0062] In both nanomesh electrodes, when tensile stress was applied, the electrical resistance increased by about 35% to 40% compared to when compressive stress was applied. Therefore, it is clear that this nanomesh electrode is useful as a detection part for a strain sensor.

[0063] The detection unit of the strain sensor may be, but is not limited to, the above-mentioned nanomesh electrode having excellent stretch resistance. Any suitable conventionally known nanomesh electrode may be used for the detection unit. [Explanation of symbols]

[0064] 10 Fiber net 11 Coated fiber netting 12 Nanomesh electrode 20. Textiles 30 Coating membrane 40 Conductive Film 110 Detection unit (nanomesh electrode) 120 Measuring section 130 Output section 140 fixed resistance 200 Measurement object 210 Cylinder

Claims

1. A fiber net is made of polyurethane and formed into a net shape. A coating film formed of polydimethylsiloxane (PDMS) that covers the fiber; and a conductive film formed on a surface of the coating film.

2. The diameter of the fibers is in the range of 100 nm to 1 μm; The thickness of the coating film is in the range of 30 nm to 300 nm.

2. The electronic functional component according to claim 1.

3. The fiber network is formed into a sheet shape, 3. The electronic functional device according to claim 1, wherein the conductive film is formed on one of the main surfaces of the fiber net.

4. 3. The electronic functional device according to claim 1, wherein the conductive film is formed on both main surfaces of the fiber net.

5. A detection unit, a measurement unit, and an output unit are provided. The detection unit is attached to the object to be measured, and the electrical resistance value of the detection unit changes depending on the shape or change of the object to be measured. The measurement unit measures the electrical resistance value of the detection unit and transmits the electrical resistance value to the output unit; The output unit outputs a predetermined signal based on the electrical resistance value received from the measurement unit, A strain sensor, wherein the detection section is configured to include the electronic functional member according to any one of claims 1 to 4.

6. A method for producing the electronic functional component according to any one of claims 1 to 4, comprising the steps of: forming the fiber network by electrospinning; forming the coating film by dip coating; forming the conductive film by vacuum deposition; A method for producing an electronic functional component, comprising:

Citation Information

Patent Citations

  • Manufacturing method for flexible vibration sensor based on PVDF nanofiber

    CN105527014A

  • High-elasticity electrical-heating fiber, and its preparation method and application

    CN107447539A

  • Composite flexible transparent conductive film and preparation method therefor

    CN108074660A

  • Electronic functional member, electronic component, and wearable device

    JP2016112246A